Improving target amino acid selectivity in a permissive aminoacyl tRNA synthetase through counter-selection. Issue 17 (11th April 2017) - Sungwienwong, Itthipol; Hostetler, Zachary M.; Blizzard, Robert J.; Porter, Joseph J.; Driggers, Camden M.; Mbengi, Lea Z.; Villegas, José A.; Speight, Lee C.; Saven, Jeffery G.; Perona, John J.; Kohli, Rahul M.; Mehl, Ryan A.; et al.
Abstract : We report the selection and characterization of an improved acridon-2-ylalanine aminoacyl tRNA synthetase. Abstract : The amino acid acridon-2-ylalanine (Acd) can be a valuable probe of protein dynamics, either alone or as part of a Förster resonance energy transfer (FRET) or photo-induced electron transfer (eT) probe pair. We have previously reported the genetic incorporation of Acd by an aminoacyl tRNA synthetase (RS). However, this RS, developed from a library of permissive RSs, also incorporates N -phenyl-aminophenylalanine (Npf), a trace byproduct of one Acd synthetic route. We have performed negative selections in the presence of Npf and analyzed the selectivity of the resulting AcdRSs by in vivo protein expression and detailed kinetic analyses of the purified RSs. We find that selection conferred a ∼50-fold increase in selectivity for Acd over Npf, eliminating incorporation of Npf contaminants, and allowing one to use a high yielding Acd synthetic route for improved overall expression of Acd-containing proteins. More generally, our report also provides a cautionary tale on the use of permissive RSs, as well as a strategy for improving selectivity for the target amino acid.